IBN RUSYD (Kritik Terhadap al-Gazali dan Pengaruhnya di Eropa) - Gasim Yamani (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2020)
This article aims to explore the treasures of Ibn Rushd's philosophy of rationality versus Al-Gazali's fundamental religious thought related to 3 (three) metaphysical problems, namely: (1). Qadimnya (eternal) nature, (2) God does not need to take care of small things (3). There is no physical resurrection. To understand and know the three problems, it can be described as follows: One: Qadim or eternal nature. The scholars represented by Al-Gazali argue that God created this universe from nothing into existence. According to Ibn Rushd, the opinion of the ulama represented by Al-Gazali cannot be justified. Therefore, what is true is that there are 2 (two) substances of two things which are both eternal (eternal), namely God and Nature, although the nature of God is not the same as the nature of Nature. The existence of God was earlier while the existence of Nature was later or later. Initially, God and finally Nature are not in terms of time or time, but from the side of the level of matter, as previously the movement of a person with the movement of his shadow. In fact, a person's movement occurs first, followed by a moving image, but both of them move at the same time and time. Although it is different from the side of its origin. Second: God doesn't have to take care of little things. Al-Gazali argues that knowledge is something that stands alone, even though it has a relationship or relationship with matter, science stands alone, the matter stands alone, but both of them manifest in one substance. Therefore, God is obliged to know everything big and small. Third: Resurrection of the body. Al-Gazali argues that the bodily awakening coincides with the spirit. This reasoning is based on a large number of texts from the Al-Qur'an which informs about the awakening between the body and the spirit. This is as informed by God through the incident of the Prophet Moses who asked God so that God could show Prophet Moses how God brought life to the dead. The Lord answered, O Moses, chop a bird then put the bird's flesh separately into all the mountains, after that call the bird, surely the meats that you spread will gather together and immediately come before you. When the Prophet Musa cried out to the bird, suddenly the meat quickly moved to one another to become a bird as before.